2015
DOI: 10.1177/229255031502300104
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to plastic surgery during undergraduate medical training: A single-institution review

Abstract: Background Applications to surgical residency programs have declined over the past decade. Even highly competitive programs, such as plastic surgery, have begun to witness these effects. Studies have shown that early surgical exposure has a positive influence on career selection. Objective To review plastic surgery application trends across Canada, and to further investigate medical student exposure to plastic surgery. Methods To examine plastic surgery application trends, national data from the Canadian R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…5,6 There have been a wide range of proposed explanations for the declining number of medical students matriculating into surgical residencies, including lifestyle, overall interest, the duration of training, lack of early surgical exposure, availability of positions upon completion of training and more. [7][8][9][10][11][12][13][14] While CaRMS publishes annual reports on the number of students applying and matching to residency positions across Canada, there are few xx published studies examining trends over a recent period of time. The existing studies have mainly focused on factors influencing medical students interest in surgery or have been specialty-specific in nature.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 There have been a wide range of proposed explanations for the declining number of medical students matriculating into surgical residencies, including lifestyle, overall interest, the duration of training, lack of early surgical exposure, availability of positions upon completion of training and more. [7][8][9][10][11][12][13][14] While CaRMS publishes annual reports on the number of students applying and matching to residency positions across Canada, there are few xx published studies examining trends over a recent period of time. The existing studies have mainly focused on factors influencing medical students interest in surgery or have been specialty-specific in nature.…”
Section: Introductionmentioning
confidence: 99%
“…The challenge then is for the present surgery educators to influence interests among medical students by early exposure, 6,7 to impart mentoring by role models, 2,4 and to provide a more positive perception of the profession. 5 Regardless of gender, there should be equal opportunities for medical students to identify their interests early on in training by laboratory 8 and operative exposure.…”
mentioning
confidence: 99%
“…49 Furthermore, studies assessing plastic surgery mentorship have revealed that learner motivation to pursue the specialty heavily relies on guidance and support from mentors, as well as operative exposure to the field. 9,[15][16][17][19][20][21][22] If opportunities to gain exposure to the comprehensive scope of the specialty are not afforded, medical students are less likely to be wellinformed for a successful match. As the number of applicants to integrated plastic surgery programs increases, a more comprehensive understanding of what plastic surgery involves becomes increasingly more important.…”
Section: Discussionmentioning
confidence: 99%